2020
DOI: 10.37190/abb-01543-2020-02
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the material’s stiffness on stress-shielding in osseointegrated implants for bone-anchored prostheses: a numerical analysis and initial benchmark data

Abstract: Purpose: This study attempted to establish the link between design of implants for bone-anchored prostheses and stress-shielding, affecting the stability of the bone-implant coupling using numerical approach. The objectives were to share a numerical model capable to evaluate the long-term stability of implants and to use this model to extract data sets showing how shape and material stiffness of threaded, press-fit and modular press-fit implants affect stress-shielding intensity. Methods: Three designs were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Further studies could associate the loading profiles with complementary mechanical (e.g., dynamics, kinematics, kinetics characteristics), physiological (e.g., electromyography of residuum muscles, metabolic energy consumption) and participant's experience (e.g., comfort score) information (Butowicz et al, 2020;Dumas et al, 2009;Dumas et al, 2017;Frossard et al, 2011b;Kaufman et al, 2018;Pantall et al, 2011). Establishing how prosthetic loading with state-of-the-art components influence the development of osseointegration around the implant and overall stability will be particularly valuable (e.g., modelling) (Helgason et al, 2009;Lee et al, 2008a;Newcombe et al, 2013;Prochor et al, 2020;Robinson et al, 2020a;Schwarze et al, 2014).…”
Section: Future Studiesmentioning
confidence: 99%
“…Further studies could associate the loading profiles with complementary mechanical (e.g., dynamics, kinematics, kinetics characteristics), physiological (e.g., electromyography of residuum muscles, metabolic energy consumption) and participant's experience (e.g., comfort score) information (Butowicz et al, 2020;Dumas et al, 2009;Dumas et al, 2017;Frossard et al, 2011b;Kaufman et al, 2018;Pantall et al, 2011). Establishing how prosthetic loading with state-of-the-art components influence the development of osseointegration around the implant and overall stability will be particularly valuable (e.g., modelling) (Helgason et al, 2009;Lee et al, 2008a;Newcombe et al, 2013;Prochor et al, 2020;Robinson et al, 2020a;Schwarze et al, 2014).…”
Section: Future Studiesmentioning
confidence: 99%
“…45 Fittings of BAP must be made with additional constraints to limit unwanted loads, leading to increased risks for the boneimplant interface (e.g., loosening, breakage of connector and safety device, periprosthetic fractures, infection, removal). [46][47][48][49][50] Altogether, this study showed that the provision of BAP has the potential to be slightly outside the usual scope of practice of prosthetists. 51 Training opportunities by qualified experts, guidelines from suppliers of implants, and formal recommendations from governing bodies about prosthetic care of consumers fitted with BAP and business management that could help reduce risks are sparse, or even missing, in some jurisdictions.…”
Section: Role Of Prosthetistsmentioning
confidence: 69%
“…The intention was to provide knowledge on how the careful selection of design features can minimize the risk of bone or implant fracture during use. This study contrasts earlier FEbased studies which have been either case studies with subject specific anatomy [25]- [32], studies focused exclusively on bone remodelling around the implant [31], [33], or FE-implementations with too low resolution to accurately capture the stress in the threaded region [25], [27]- [30], [32], [34]- [37].…”
Section: Introductionmentioning
confidence: 73%